PELATIHAN POSITIVE EXPECTATION BAGI GURU SEKOLAH MARDI YUANA CILEGON UNTUK MENCAPAI TUJUAN PEMBELAJARAN [POSITIVE EXPECTATION TRAINING FOR TEACHERS IN MARDI YUANA CILEGON SCHOOL TO ACHIEVE LEARNING OBJECTIVE] - Bertha Natalina Silitonga; Juniriang Zendrato; Asih Enggar Susanti; Juliana Suhindro Putra (Jurnal Sinergitas PKM & CSR, 2020)
Teachers of Mardi Yuana Cilegon School have gaps in all areas of teaching, namely: 1) Affection domain, where the teacher appears dominant in dealing with students, fellow teachers, parents, and leaders; 2) Psychomotor domain, where the affection problem has an impact on class management skills (the teacher arranges the class according to his own will without thinking about the learning objectives); 3) Cognitive domain, where affection problems also have an impact on the preparation of lesson plan (teachers feel that they have mastered the subject matter so they are not interested in learning anymore). Because impactful learning is heart-to-heart, this teacher training is focused on managing affection (positive expectation) to support classroom teaching. Thus, the aim of this training is to introduce and train teachers to practice effective affection management. This training was held eight times (January-April 2019) with seventy teachers from kindergarten to junior high school at Mardi Yuana Cilegon School. The teacher training materials provided are: 1) The importance of having positive expectations; 2) How to help students succeed; 3) How to appear in class; 4) How to make students interested in learning; 5) How to increase students' positive behavior. The result of observations during learning is that the teachers look enthusiastic about learning new things. The result of the implementation evaluation shows an increase in teacher understanding of positive expectations in the learning process.BAHASA INDONESIA ABSTRACT: Guru Sekolah Mardi Yuana Cilegon memiliki kesenjangan di semua ranah pengajaran, yaitu: 1) Ranah afeksi, dimana guru tampak dominan di dalam berelasi dengan siswa, sesama guru, orangtua, dan pimpinan; 2) Ranah psikomotorik, dimana masalah afeksi tersebut berdampak pada keterampilan pengelolaan kelas (guru mengatur kelas menurut keinginannya sendiri tanpa memikirkan tujuan pembelajaran yang ada); 3) Ranah kognitif, dimana masalah afeksi juga berdampak pada penyusunan rencana pembelajaran (guru merasa sudah menguasai materi pelajaran sehingga tidak berminat untuk belajar lagi). Oleh karena pembelajaran yang berdampak adalah dari hati ke hati, maka pelatihan guru ini difokuskan pada pengelolaan afeksi (positive expectation) untuk mendukung pengajaran di kelas. Sehingga, tujuan pelatihan ini adalah memperkenalkan dan melatihkan praktik-praktik pengelolaan afeksi yang efektif kepada guru. Pelatihan ini diadakan sebanyak delapan kali (Januari-April 2019) dengan peserta sebanyak tujuh puluh orang guru dari TK-SMP di sekolah Mardi Yuana Cilegon. Materi pelatihan guru yang diberikan adalah: 1) Pentingnya memiliki ekspekstasi positif; 2) Bagaimana membantu siswa agar berhasil; 3) Bagaimana berpenampilan di kelas; 4) Bagaimana membuat siswa tertarik untuk belajar; 5) Bagaimana meningkatkan perilaku positif siswa. Hasil pengamatan selama pembelajaran adalah para guru terlihat antusias mempelajari hal baru. Hasil evaluasi pelaksanaan menunjukkan adanya peningkatan pemahaman guru mengenai positive expectation di dalam proses pembelajaran.